The Influence of Ethical Leadership on Employee Performance through Organizational Citizenship Behavior and Intrinsic Motivation - Gabriely Elyas Tangkawarow; Sherly Rosalina Tanoto (Petra International Journal of Business Studies, 2023)
Employee performance and its antecedents have always been exciting research topics as employee performance impacts organizational success. Concerning this, leaders are considered to have a significant role in influencing employee performance. Despite being extensively discussed in the literature, little research has investigated ethical leadership as a construct. This research examines the impacts of ethical leadership, organizational citizenship behavior, and intrinsic motivation on performance. The novelty of this research is that it uses two mediating variables that have never been used to examine the association between ethical leadership and performance. A quantitative method was used, and data was collected using a survey. Results indicated that ethical leadership affected organizational citizenship behavior and intrinsic motivation but did not affect employee performance. Ethical leadership influences employee performance if mediated by organizational citizenship behavior. These results may provide new insights for scholars and leaders. Theoretically, this study is one of a few attempts to understand the link between ethical leadership and performance, especially in Eastern culture. Our study suggests leaders should demonstrate ethical leadership to promote OCB and employee motivation.